Análisis, diseño e implementación de una aplicación web para la administración de un condominio, además de una aplicación móvil para el envío de notificaciones - Ortega Loachamín, Henry Javier (2017)
The present job tries to explain the acquired knowledge in the career of Systems Engineering trough the analysis, develop and implementation of a web oriented computer application and to mobile devices for the administration of a condominium, taking as reference the requirements of the “Torres de Aranjuez” building, a housing set located in the south of Quito. The current situation of the condominiums administration is analyzed in the first part, and the need for the construction of a technological tool that helps to improve the process involved in it, with the aim of improve the information’s treatment, centralize it and thus better organized, this allows to perform searches and generate a set of reports that permits the construction of data indicators, in addition to improving the communication between condominium’s users and the administrator through the use of the mobile app for sending notification. At the end of development cycle and after undergoing several software tests, a stable and robust application will be obtained, that fulfill the needs of the housing complexes management, as well as being the basis for the construction of future projects of the “Universidad Politécnica Salesiana”.